Leadership and Organization in Islamic Education (Lembaga Pengembangan Kinerja Dosen, 2025)
Leadership and organizational structure in Islamic education are two interrelated elements that shape the direction, vision, and sustainability of educational institutions founded upon divine values. The background of this study stems from the phenomenon of weak leadership systems and organizational governance in several Islamic educational institutions in Indonesia, characterized by low managerial competence and the lack of integration of spiritual values in leadership practices. This condition hampers institutional effectiveness in achieving the expected quality of education. The purpose of this research is to analyze the role of leadership as a pillar of spiritual and managerial transformation and to describe the organizational system of Islamic education as a collaborative and value-based system. This study employs a qualitative method with a literature review approach, analyzing various academic sources, Islamic leadership theories, and previous research findings. The results indicate that Islamic educational leadership grounded in the values of amanah (trustworthiness), syura (consultation), and ukhuwah (brotherhood) plays a crucial role in building a productive and ethical organizational culture. Furthermore, an organization based on collaboration, justice, and open communication strengthens institutional effectiveness and enhances the participation of all educational components. The synergy between spiritual leadership and a value-driven organizational system produces Islamic educational institutions that are excellent, adaptive, and oriented toward nurturing individuals who are both faithful and knowledgeable.